Herrens Veje: A catalyst to reflect upon military chaplaincy and ecclesial issues in a Nordic context - Grimell, Jan (The journal of religion and film, 2023)
This article is based on an analysis of the first season of the Danish series Herrens Veje (The Way of the Lord; Price 2017). The series portrays the young, idealistic pastor and military chaplain August, who is deployed to a conflict zone with a military unit. He accompanies the unit on a patrol to win the trust of the soldiers. During the patrol, they engage in combat and August kills an innocent civilian woman. Upon return, the transition from military to civilian life proves to be increasingly challenging and troublesome. As the series proceeds, August’s mental health deteriorates and his suffering increases. In this article, August’s traumatic transition is analyzed by using four different conceptual perspectives that uncover the specifics of trauma and identity: PTSD, moral injury, spiritual injury and the combat trauma itself. We argue that several factors are portrayed in the series as unnecessarily complicating and worsening August's condition and life situation. Firstly, he is affected by a harmful theological understanding of mental health due to combat trauma, and secondly, by ecclesiological and folk church specifics such as a bureaucratic mindset and a focus on hierarchy and status. The implications of the analysis are discussed both on micro and macro levels. Our aim with analyzing trauma in fiction material is to demonstrate how fiction presents real life dilemmas and situations in concentrated, often dramatized ways. This makes such material useful for reflections on "actual" military chaplaincy and ecclesiology.